2020
DOI: 10.1177/1934578x20913453
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucosidase Inhibitory and Glucose Uptake Stimulatory Effects of Phenolic Compounds From Dendrobium christyanum

Abstract: A methanolic extract from the dried root of Dendrobium christyanum Rchb.f. (Orchidaceae) exhibited α-glucosidase inhibitory activity and glucose uptake stimulatory effect. Chromatographic separation of the extract led to the isolation of 13 phenolic compounds (1-13). Their structures were determined by spectroscopic analysis. The isolates were then evaluated for in vitro α-glucosidase inhibitory and glucose uptake stimulatory activities. Methyl haematommate (1), methyl 2,4-dihydroxy-3,6-dimethylbenzoate (3), n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…However, introducing methoxy groups to C-3 and C-5′ of 9 caused a total loss of activity, as seen in dihydrosinapyl dihydroferulate ( 4 ). A similar phenomenon, in which the presence of aromatic methoxy groups diminished α -glucosidase inhibitory activity, was earlier reported for p -coumarate esters of long-chain alcohols [ 71 ].…”
Section: Resultssupporting
confidence: 78%
“…However, introducing methoxy groups to C-3 and C-5′ of 9 caused a total loss of activity, as seen in dihydrosinapyl dihydroferulate ( 4 ). A similar phenomenon, in which the presence of aromatic methoxy groups diminished α -glucosidase inhibitory activity, was earlier reported for p -coumarate esters of long-chain alcohols [ 71 ].…”
Section: Resultssupporting
confidence: 78%
“…Interestingly, mangiferin (7) displayed a strong neuroprotective activity, with a 60.5 ± 1.7% The isolated compounds were further studied for antidiabetic potential. Compounds 3-7 were evaluated for α-glucosidase inhibitory activity using established protocols [21,22]. The alkaloids 1 and 2, however, were not tested due to their limited amounts.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Recently, we have found that some α-glucosidase inhibitors (AGIs) of natural origin also possessed the ability to stimulate glucose uptake by skeletal muscle cells [21,22]. This secondary biological activity has currently attracted research attention because it might help to increase the antidiabetic potential of these AGIs.…”
Section: Biological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several plant secondary metabolites of different classes have been investigated as potential candidates for AGI drug development. Interestingly, a great number of phytochemicals obtained from the Orchidaceae family have been found to possess strong α -glucosidase inhibitory activity [ 3 , 4 , 5 ]. Orchidaceae is one of the largest families in the plant kingdom and consists of about 735 genera and more than 20,000 species [ 6 ].…”
Section: Introductionmentioning
confidence: 99%